Adoption and use of emerging cultural technologies in China's museums - Ch’ng, Eugene; Cai, Shengdan; Leow, Fui-Theng; Zhang, Tong Evelyn (Elsevier, 2018)
Our article maps the well-being of the adoption and use of digital technologies in museums in China. Digital technologies used here are termed ‘cultural technology’ in top-level national policies for the creative cultural industry, with culture and heritage at the core of all such activities. Our investigation aims to understand the present state of adoption and use of cultural technologies with the goal of identifying limitations so as to provide a roadmap for the informed design and development of museum-based digital exhibits that are appropriate for visitors. Whilst our study is focused on China's museums, our evaluation model and lessons learned can be used as comparative studies for museums globally. This highlights the novelty of our article, for the scale of which we carried out our evaluation has never been conducted before. We travelled 22 sites over 15 cities and collected over 800 samples of data. We evaluated 36 digital systems used by over 800 visitors and observed how users interacted and engaged with the systems with a record of 21 variables related to the length of interaction, engagement, quality of contents and types of systems, age groups, sexes, and the number of participants and whether they were individuals or in groups. Our investigation revealed important findings in both digital systems and visitor engagement.